The role of university-firm relations to foster regional development: evidence from Brazilian Amazon - Ana Paula Bastos; Leandro Almeida; Marcia Diniz; Marcelo Diniz (European Regional Science Association (ERSA), 2012)
The role of universities for the innovation process of countries or regions had been widely explored. In lagged regions becomes a reference not only for qualification and research but concentrates brains and fixes qualified people. This paper analyses innovation and especially the interaction of firms with universities and research institutes, as strategy to face the low internal investment capacity in innovation. Our focus is the ultra-peripheral region of Brazilian Amazon and it is part of a larger research project which investigates these interactions internationally. The interest in studying these interactions in Brazil are based on findings that the investments in R&D by the private sector are low, and the national (and thus regional) innovation systems are immature (Albuquerque, 1998). Data was collected based on a questionnaire applied to firms, adapted by Federal University of Minas Gerais, Brazil from the Carnegie Mellon (Cohen, 2002) and Yale Surveys (Klevorick, 1995) on firms' interaction. The sample was taken from a database of university-based research groups registered in CNPq (national agency of research funding), that declared some kind of innovative relationship with firms. Although, the interaction between universities and firms has been considered crucial for the development of innovation, we found very few interactions resulting in a low complementary role or even substitute R&D efforts of these firms. Results show that the continuous interactions between firms and university are restricted to agronomy, energy, electrical and mining engineering. And that the role of university in leading the process is not sufficient to suppress the peripheral condition of the Amazon region.
Keywords: 330